2016
DOI: 10.1021/acs.inorgchem.6b00839
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of Cesium, Lithium/Cesium, and Sodium/Cesium Bis(trimethylsilyl)amide (HMDS) Complexes

Abstract: Reacting cesium fluoride with an equimolar n-hexane solution of lithium bis(trimethylsilyl)amide (LiHMDS) allows the isolation of CsHMDS (1) in 80% yield (after sublimation). This preparative route to 1 negates the need for pyrophoric Cs metal or organocesium reagents in its synthesis. If a 2:1 LiHMDS:CsF ratio is employed, the heterobimetallic polymer [LiCs(HMDS)2]∞ 2 was isolated (57% yield). By combining equimolar quantities of NaHMDS and CsHMDS in hexane/toluene [toluene·NaCs(HMDS)]∞ 3 was isolated (62% yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 74 publications
1
41
1
Order By: Relevance
“…These K-N bond distances are similar to those found for the solvent-free (KHMDS) 2 [2.770(3) and 2.803(3) Å]. 33 The distinct K-N bond lengths for K1 and K2 observed in 1 result in two slightly distinct N-K-N angles [N-K1-N 94.58 (4) and N-K2-N 95.13(4)°], whilst the K-N-K 34,36,39,41,49,56,68,69 3 crystallises as a dimeric (KHMDS) 2 unit, and it contains two molecules of THF, one coordinating to each K atom (Fig. 3a) ] unit represents a branch point towards four distinct directions in the polymeric two-dimensional sheet, two through its K atoms and two via two methyl groups from each HMDS ligand.…”
Section: X-ray Diffraction Studiessupporting
confidence: 70%
See 2 more Smart Citations
“…These K-N bond distances are similar to those found for the solvent-free (KHMDS) 2 [2.770(3) and 2.803(3) Å]. 33 The distinct K-N bond lengths for K1 and K2 observed in 1 result in two slightly distinct N-K-N angles [N-K1-N 94.58 (4) and N-K2-N 95.13(4)°], whilst the K-N-K 34,36,39,41,49,56,68,69 3 crystallises as a dimeric (KHMDS) 2 unit, and it contains two molecules of THF, one coordinating to each K atom (Fig. 3a) ] unit represents a branch point towards four distinct directions in the polymeric two-dimensional sheet, two through its K atoms and two via two methyl groups from each HMDS ligand.…”
Section: X-ray Diffraction Studiessupporting
confidence: 70%
“…A total of eleven new solvates of KHMDS (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) have been prepared and structurally characterised, both in solution and in the solid state. All synthetic protocols were optimised for obtaining high-quality crystalline samples for single crystal X-ray diffraction studies.…”
Section: Synthetic Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…OHara and coworkers have demonstrated that CsN(SiMe 3 ) 2 could be obtained by metathesis between LiN(SiMe 3 ) 2 and CsF. [21] We ascribe the success of this indole synthesis to the enhanced reactivity of CsN(SiMe 3 ) 2 over LiN(SiMe 3 ) 2 .T he conditions in entry 4w ere next used to probe the impact of substrate stoichiometry.I ncreasing the loading of LiN(SiMe 3 ) 2 from 1t o2equiv improved the AY of 3aa to 64 %( entry 7). Further increasing the loading to 3equiv,h owever, had ad etrimental impact on the AY (entry 8).…”
mentioning
confidence: 97%
“…Other combinations either gave low AYs of 3 aa (entries 5 and 6) or did not promote the reaction at all (see the Supporting Information for details). O'Hara and co‐workers have demonstrated that CsN(SiMe 3 ) 2 could be obtained by metathesis between LiN(SiMe 3 ) 2 and CsF . We ascribe the success of this indole synthesis to the enhanced reactivity of CsN(SiMe 3 ) 2 over LiN(SiMe 3 ) 2 .…”
Section: Methodsmentioning
confidence: 93%